Phytocritical Examination of Plant Consciousness in The Island of Missing Trees - Sharma, Kamal (Molung Educational Frontier, 2026)
This paper explores plant consciousness and sentience in Elif Shafak’s novel The Island of Missing Trees by drawing on the theoretical insights developed under the rubric of phytocriticism, specifically focusing on plant personhood and plant agency. Phytocritical examination of literature involves exploring tree sentience, consciousness, and agency. In this regard, this paper argues that the plant, specifically the Fig Tree, emerges as an active, sentient agent of the botanical world that exists independently beyond human measure, witnessing human love, war, and trauma, along with arboreal suffering. The tree, then, is not merely a setting, but a character having knowledge of both the plant and human worlds. As shown in the novel, the Fig Tree brought to London from Cyprus tells the part of the story in the first person as a wise and observant narrator. It is a witness for Kostas and Defne’s affairs in Cyprus, and their daughter, Ada’s, growing up in London. Recognizing plants’ agency and sentience is a part of phytocritical exploration as discussed by Michael Marder, Peter Wohlleben, and Matthew Hall. Theoretically, phytocriticism, a branch of ecocriticism, recognizes plants as persons. Whollenban’s plant sentience and communicative virtues, Hall’s exploration of plants as persons, Marder’s idea of plants’ sentience, and Kallhoff’s discussion of plant language, which is ‘no language of sounds’, serve to establish plants as social beings with communicative capabilities, thereby narrating and witnessing their own histories and human histories/world.